Contemporary Refugee‐Border Dynamics and the Legacies of the 1919 Paris Peace Conference1. Issue 4 (12th July 2019) - Culcasi, Karen; Skop, Emily; Gorman, Cynthia
Abstract: While the geopolitical legacies of the World War I peace negotiations are widely recognized, this article examines the often overlooked connection between the WWI Paris Peace Conference's spatial and geopolitical logics and contemporary refugee‐border dynamics. We argue that the spatial and geopolitical logics that framed the WWI Paris Peace Conference—the creation of new states, the propagation of the Western ideal of bounded sovereign states, the nationalist goals of self‐determination and homogeneous ethnic nations, and the establishment of a system of international governance—continue to impact refugee‐border dynamics and "crises" today. The categories, ideals, and practices of the international refugee regime that emerged over the last one‐hundred years stem in great part from these logics. In this paper, we urge critical contemplation about how these foundations—including the establishment of the post of High Commissioner for Refugees in 1921, the resultant Nansen Passports, the post‐WWI minority treaties, and lastly the 1933 Convention Relating to the International Status of Refugees—connect to contemporary human (im)mobility and border violence. We also introduce the articles in this special issue and highlight key themes and future directions for research in critical migration studies.